The relationship between mastitis and the B-mode, colour Doppler ultrasonography measurements of supramammary lymph nodes in cows - Risvanli, Ali; Dogan, Halef; Safak, Tarik; Kilic, M. Akif; Seker, Ibrahim (Cambridge Univ Press, 2019)
This research communication aims to test the hypothesis that B-Mode, colour Doppler ultrasonographic measurements and characteristics can identify mastitis in dairy cows. A total of 102 lactating cows were divided into 3 groups: cows in which all mammary quarters were CMT-negative, cows with CMT-positive mammary quarters and cows with clinical mastitis in at least one quarter. Colour Doppler ultrasonography measurements of the supramammary lymph nodes revealed that distortion-type vascular morphology, the rate of type 4 vascular densities and the incidence of mixed-type vascular distributions were highest in the clinical mastitis group, whereas the frequency of avascularity in supramammary lymph nodes was highest in the CMT-negative group. All differences were significant. In conclusion, the use of B-mode and colour Doppler ultrasonographic measurements of the supramammary lymph nodes can provide useful information about the current condition of mastitis in cows, although its diagnostic potential remains to be determined.
Keywords: Cows; Doppler; mastitis; ultrasonography